PERAN KINERJA KEUANGAN DALAM PENINGKATAN NILAI PERUSAHAAN PADA SEKTOR CONSUMER GOODS - Karunia, Hendrico Halif; Setiawan, Wahyu (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2025)
Companies from various sectors from small, medium to large scale assess their business success, one of which is the company's financial performance. In order to realize the company's vision and mission, good and healthy financial performance is needed. This research aims to examine how financial performance affects the value of the company. This research will take a sample of companies listed on the Indonesia Stock Exchange in the consumer goods sector. This research uses multiple linear regression analysis with a significance level of 5%.